Hybrid composites of silica glass fibre/nano-hydroxyapatite/polylactic acid for medical application - He, Lizhe; Chenhai, Zhu; Cong, Xiaoye; Rudd, Chris D.; Liu, Xiaoling (2017)
Fibre reinforced composites (FRC) have shown great potential for the application of internal bone fixation due to mechanical properties that are similar to those of human cortical bones. Ternary composites of silica glass fibres, nano-hydroxyapatite (n-HA) and polylactic acid (PLA) were prepared by compression moulding and their mechanical properties were characterized in this study. With the volumetric content of glass fibre remained constantly at 30% and the volume fraction of n-HA increased from 0% to 5%, the flexural strengths of composites decreased from 625.68 MPa to 206.55 MPa, whereas a gradual increment of flexural modulus from 11.01 to 14.08 GPa were observed at the same time. Within a 28-day degradation period, the flexural strengths decreased by 30%, while no obvious trend of modulus variation was found. The flexural properties of all composites prepared in this study were all found to be close to the reported flexural properties. On the other hand, as more n-HA were incorporated, the water absorption percentages increased, whereas negligible mass loss were recorded. SEM images revealed that the impregnation of fibre mats was poor as loose fibres were observed, which shall be solved in future research to further improve the mechanical properties as well as endurance against degradation. © 2017 International Committee on Composite Materials. All rights reserved.